Zgodovina slovenskega verza - skica - Bjelčevič, Aleksander (Slavistična revija, 1997)
The article outlines the history of the Slovene vers: from the folk poem set to music, through Protestant syllabism, tonic and syllabotonic verse of the 19th c., to free verse in the 20th c.
Keywords: literarne študije; Lithuanian Metrica; metrika; Slovene literature; slovenska književnost; slovenska poezija; slovenski verz; verzologija; zgodovinski pregledi